Multi-Objective Optimisation of Hot Forging Processes using a Genetic Algorithm - C. F. Castro (2010)
Searching for good design solutions within the industrial forging environment is necessary to improve the quality and overall productivity of the processes. Multi-objective optimisation design for multi-stage processes is a complex problem involving large number of design variables and sequential relationships between any two stages. The aim of this paper is to propose a novel framework to handle real-life hot forging optimisation problems considering a genetic algorithm based technique. A Pareto-based multi-objective optimisation model for multi-stage hot forging processes is developed. Using a case study of a two stage forging upsetting, the algorithm has been able to converge to the Pareto front identifying near optimal designs for the forging process.